Antimicrobial activity of some essential oils against Streptococcus agalactiae, an important pathogen for fish farming in Brazil - Majolo, Cláudia; Pilarski, Fabiana [UNESP]; Chaves, Francisco Célio Maia; Bizzo, Humberto Ribeiro; Chagas, Edsandra Campos (Taylor & Francis, 2018)
The antimicrobial activity of the essential oils from Lippia alba, Lippia sidoides, Mentha piperita, Ocimum gratissimum and Zingiber officinale was tested against Streptococcus agalactiae. The major compounds in the oils, identified by gas chromatography and mass spectrometry (GC/MS), were geranial (25.4%), neral (16.6%) and caryophyllene oxide (16.0%) in L. alba; thymol (76.6%), p-cymene (6.3%) and β-caryophyllene (5.0%) in L. sidoides; menthol (30.5%), menthyl acetate (14.6%), pulegone (14.2%) and menthone (12.9%) in M. piperita; eugenol (43.3%), 1,8-cineole (28.2%) and β-selinene (5.5%) in O. gratissimum; and geranial (23.2%), neral (16.7%) and 1,8-cineole (15.8%) in Z. officinale. All essential oils evaluated showed bactericidal action against S. agalactiae with minimum inhibitory concentration (MIC) ranging from 312.5–2,500 μg mL−1 and minimum bactericidal concentration (MBC) ranging from 416.7–2,500 μg mL−1. In this study, L. sidoides essential oil showed the better results against S. agalactiae.
Keywords: antimicrobial activity; essential oil composition; group B Streptococcus; Medicinal plants